Tricksters and Estates : On the Ideology of Restoration Comedy. - Canfield, J. Douglas (The University Press of Kentucky, 2015)
If the Renaissance was the Golden Age of English comedy, the Restoration was the Silver. These comedies are full of tricksters attempting to gain estates, the emblem and the reality of power in late feudal England. The tricksters appear in a number of guises, such as heroines landing their men, younger brothers seeking estates, or Cavaliers threatened with dispossession. The hybrid nature of these plays has long posed problems for critics, and few studies have attempted to deal with their diversity in a comprehensive way. Now one of the leading scholars of Restoration drama offers a cultural h.